2020
DOI: 10.1039/c9mh01268k
|View full text |Cite
|
Sign up to set email alerts
|

A bipolar host based high triplet energy electroplex for an over 10 000 h lifetime in pure blue phosphorescent organic light-emitting diodes

Abstract: Ultimate device performances of blue phosphorescent organic light-emitting diodes, an external quantum efficiency of 27.6%, a device lifetime over 10 000 h at 100 cd m−2, and CIE (0.12, 0.13), were achieved by employing an electroplex host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 35 publications
3
97
0
Order By: Relevance
“…C3 is reported as a robust host even for pure blue phosphorescent OLEDs. 48 The superior molecular stability of C4 to A4 has been demonstrated above. Previously, we suggested that PO groups would undermine the molecular stability due to the low BDEf of C−P bonds.…”
Section: Implications For Rational Design Of Robust Oled Materialsmentioning
confidence: 82%
“…C3 is reported as a robust host even for pure blue phosphorescent OLEDs. 48 The superior molecular stability of C4 to A4 has been demonstrated above. Previously, we suggested that PO groups would undermine the molecular stability due to the low BDEf of C−P bonds.…”
Section: Implications For Rational Design Of Robust Oled Materialsmentioning
confidence: 82%
“…Till date, several molecular design approaches have been reported for the development of stable and high E T hosts for blue PhOLEDs, in which the design featuring chemically stable and high E T building units with nonconjugative mode of connectivity is attractive. [ 24–35 ] Commonly, carbazole has been employed as an electron donor for constructing blue host materials due to its high E T , excellent hole transporting property, amorphous nature, good thermal stability, and wide scope for chemical modification. [ 4–6,24–35 ] As an electron acceptor units, aryltriazine, phosphine oxide, and cyano units have been widely used as the electron transporting units for blue hosts.…”
Section: Introductionmentioning
confidence: 99%
“…As the exciton converting materials, phosphors and TADF emitters have been employed. [ 13,14 ] The phosphors can convert all excitons into radiative triplet excitons by intersystem crossing and the TADF emitters can transform all excitons into radiative singlet excitons by reverse intersystem crossing (RISC). The secondary phosphors and TADF emitters have been specified as an assistant dopant or sensitizer in the literatures.…”
Section: Introductionmentioning
confidence: 99%